Extensions of Lattice Set Functions to Regular Borel Measures - Maritz, P. (Journal of Informatics and Mathematical Sciences, 2012)
This paper deals with the unique extension of a finite regular set function from the $δ$-lattice of all compact $G_δ$-subsets of a locally compact Hausdorff space to a finite regular measure on the $δ$-ring of all relatively compact Borel subsets of the space. This extension is a two-step method because it is performed (without density assumptions) via the $δ$-ring of all relatively compact Baire subsets of the space.